The Effects Of Kelakai Leaf Infusion Kalakai (Stenochlaena palustris (Burm.F) Bedd) On The Levels of AST and ALT Enzymes in Wistar White Rats Induced with CCl4 - Salsabila, Ivah; Carmelita, Austin Bertilova; Shinta, Herlina Eka; Toemon, Angeline Novia; Praja, Rian Ka (Barigas: Jurnal Riset Mahasiswa, 2025)
The liver plays a crucial role in the body, including protein synthesis, bile secretion, metabolism, and xenobiotic excretion, making it susceptible to damage from exposure to toxic substances. Carbon tetrachloride (CCl4) is a free radical known to cause liver injury. Abundant in Kalimantan, kelakai contains flavonoids, alkaloids, steroids, and tannins, suggesting its metabolites may have hepatoprotective potential. This study aimed to assess the antioxidant content of kelakai leaf infusion for potential protection CCl4-induced liver damage. Kelakai leaves (Stenochlaena palustris (Burm.F) Bedd). were infused at a 20% concentration, then divided into three different doses: P1 (300 mg/kgBW), P2 (400 mg/kgBW) and P3 (5—mg/kgBW). The 14-day study evaluated whether kelakai leaf infusion could prevent the elevation of AST dan ALT enzyme ativities. The results indicated increased levels of AST dab AKT enzymes in each treatment group. Though the statistical analisis showed non-significant differences.